Alterations in muscular enzymes of horses competing long-distance endurance rides under tropical climate - Teixeira Neto, Antônio Raphael [UNESP]; Ferraz, G. C. [UNESP]; Moscardini, A. R. C.; Balsamão, G. M.; Souza, J. C. F.; Queiroz-Neto, A. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2008)
Estudaram-se as alterações de atividade das enzimas musculares creatino quinase (CK), lactato desidrogenase (LDH) e aspartato aminotransferase (AST) em um grupo de cavalos que utilizados em provas de enduro de 70 e 100km de distância, em cinco competições. Os valores (U/l) basais (antes da largada) foram 245,13±9,84 para CK, 496,61±14,76 para LDH e 328,95±8,65 para AST. Todas as atividades das enzimas decresceram no primeiro momento das provas (~30km). Valores de pico, significativamente diferentes, foram alcançados para CK (413,59±50,75) imediatamente após 70km de distância; 24 horas após para LDH (628,61±33,30); e 48 horas após as provas para AST (389,89±16,96). A monitoração do período de recuperação revelou diferente comportamento entre as concentrações enzimáticas com CK retornando aos valores basais 24 horas pós-provas (279,61 ± 23,05). LDH e AST retornaram aos valores basais, 72 horas pós-provas (505,25±33,78 e 359,35±24,90, respectivamente). Os dados obtidos revelaram diferentes alterações na concentração de enzimas musculares de cavalos de enduro, diretamente relacionadas com a duração do esforço.

This study tried to monitor the alterations of muscle enzymes activity - creatinokinase (CK), lactate dehydrogenase (LDH), and aspartate aminotransferase (AST) - in a group of horses that participated of 70 and 100km distance rides in five competitions of an annual endurance championship under tropical climate. Pre ride levels (U/l) were 245.13±9.84 for CK, 496.61±14.76 for LDH, and 328.95±8.65 for AST. When compared to these levels, the results revealed a significant decrease in all enzymes activities in the first moment of the rides. Peak levels, significantly different, were reached, immediately after rides by CK (413.591±50.75); 24 hours post rides by LDH (628.61±33.30); and 48 hours after rides by AST (389.89±16.96). Monitoring of recovery period revealed different behavior among enzymes activities with CK values returning to pre ride values (279.61±23.05) 24 hours post rides, while LDH and AST values returned to pre ride values (505.25±33.78 and 359.35±24.90, respectively) 72 hours post rides. These data revealed different alterations in concentration of muscular enzymes in endurance horses directly related to the duration of the effort.
Alterações em enzimas musculares de cavalos em competições de enduro de longa distância em clima tropical
Keywords: Horse; endurance; Enzymes; Muscle; Cavalo; Enduro; Enzimas; músculo